Safe and environment-friendly rough-surface winding core pipe and processing technology thereof

By using materials such as polyvinyl chloride, epoxy resin, neoprene and chopped fiber composites, combined with modified aramid fiber and carbon nanotube composites, the problem of insufficient strength and environmental protection performance of the core tube is solved, and the problem of insufficient core tube strength and environmental protection performance is achieved. Efficient and environmentally friendly core tube production.

CN119410083AInactive Publication Date: 2025-02-11SUZHOU TIANYU PLASTIC +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411549226.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing core tubes have poor strength and rigidity, are prone to brittle cracking, and the long glass fibers used during processing are harmful to the environment, have low production efficiency, and are prone to contamination.

Method used

Using polyvinyl chloride, epoxy resin, neoprene, chopped fiber composite, dispersant and toughener, melt blending and granulation through a twin screw extruder to prepare a rough core tube with a surface , and improve mechanical and environmental performance by modifying aramid fiber and carbon nanotube composites.

Benefits of technology

It significantly improves the mechanical and environmentally friendly performance of the core tube, improves the impact and bending strength of the core tube, and reduces the harm to the environment, improves production efficiency and reduces the risk of pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005114625570000091
    Figure BDA0005114625570000091
  • Figure BDA0005114625570000101
    Figure BDA0005114625570000101
Patent Text Reader

Abstract

The invention relates to a safe and environment-friendly rough-surface core winding pipe and a processing technology thereof. The safe and environment-friendly rough-surface core winding pipe comprises the following components in parts by mass: 160-200 parts of polyvinyl chloride, 90-100 parts of epoxy resin, 40-60 parts of chloroprene rubber, 30-40 parts of a chopped fiber compound, 10-16 parts of a dispersing agent and 8-12 parts of a toughening agent. The chopped fiber compound comprises a modified aramid fiber and carbon nanotube composite material. The method has the effects of improving the green and environment-friendly performance of the product and improving the mechanical strength of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of core-rolling tubes, and in particular to a safe and environmentally friendly core-rolling tube with a rough surface and a processing technology thereof. Background Art

[0002] A winding core tube is a device used to wind up thin films or metal foils, such as copper foil, aluminum foil and other products. When winding up, the film product needs to be manually wound onto the winding core tube, and then the equipment is started to wind the product.

[0003] Conventional core tubes are processed by extrusion molding, and the materials are mostly thermoplastic materials. After the tube is extruded and cooled, it can be cut according to the required process length to complete the production. However, the strength and rigidity of conventional core tubes are poor, and they are prone to brittle cracks after long-term use. In order to improve the strength and rigidity of the core tubes, some core tubes will add long glass fibers and other materials to improve the strength and toughness. This kind of tube is called FRP tube, which is usually wound with long glass fibers and coated with resin materials for curing. When the material is cured, it is turned to make the surface of the core tube flat while exposing the glass fibers, thereby maintaining a certain degree of roughness and improving the efficiency of the core.

[0004] However, glass fiber is a material that is harmful to the human body. It can cause harm to people if it comes into contact with the skin, eyes, mouth, or nose. In the conventional processing, the resin and long glass fiber need to be turned after being mixed and wound, which has low production efficiency. After turning, the glass fiber is exposed, and pollutants are easily contaminated on the surface, causing the winding core tube to be contaminated. At the same time, long glass fiber materials are not easy to recycle. When the tube is scrapped or damaged, it can only be buried, which is very harmful to the environment. Summary of the invention

[0005] In order to improve the environmental performance of a winding core tube, the present application provides a safe and environmentally friendly winding core tube with a rough surface and a processing technology thereof.

[0006] The present application provides a safe and environmentally friendly rough surface roll core tube and its processing technology, which adopts the following technical solutions: In the first aspect, the present application provides a safe and environmentally friendly rough surface roll core tube, which adopts the following technical solutions: A safe and environmentally friendly rough-surface rolled core tube, comprising the following components in parts by weight: 160-200 parts of polyvinyl chloride, 90-100 parts of epoxy resin, 40-60 parts of chloroprene rubber, 30-40 parts of chopped fiber composite, 10-16 parts of dispersant and 8-12 parts of toughening agent; The chopped fiber composite comprises a composite material of modified aramid fiber and carbon nanotube.

[0007] By adopting the above technical scheme, a short-cut fiber composite is added to the system. The short-cut fiber has good mechanical properties. After combining with the epoxy resin, the overall mechanical properties of the epoxy resin can be effectively improved. At the same time, the adhesion between the short-cut fiber and the epoxy resin is further improved, thereby further improving the bonding performance between the various components in the system; the modified aramid fiber has the characteristics of high strength, high modulus, high stability and good chemical stability. The aramid molecular chains form a tight crystal structure through hydrogen bonds and stacking forces. After being added, the tensile strength of the prepared winding core tube is greatly improved, and the aramid fiber has good green environmental protection performance, which can further improve the environmental protection performance of the prepared winding core tube; the carbon nanotube has a high aspect ratio, as well as good elastic modulus and mechanical properties. It can be compounded with the modified aramid fiber to improve the comprehensive performance of the system, so that the mechanical properties and strength of the prepared winding core tube are further improved.

[0008] Preferably, the chopped fiber composite is prepared by the following method: After mixing water and potassium oleate, a potassium oleate dispersion is obtained, and aramid fiber is added to the potassium oleate dispersion, subjected to plasma modification treatment, and then magnetically stirred. The aramid fiber is then filtered out, washed, and dried to obtain modified aramid fiber.

[0009] By adopting the above technical scheme, potassium oleate is prepared from sustainably grown oil crops. After the aramid fiber is modified by potassium oleate, the compatibility between the aramid fiber and the rubber matrix can be increased, thereby making the combination between the two closer. At the same time, the mechanical properties of the composite material can be further improved, and the bonding performance between the components in the winding core tube is effectively improved, and the material has green and environmentally friendly properties; aramid has a polymer structure of amide chains, so that the fiber surface usually carries some polar negative charges, so that the hydrophilic head in potassium oleate can be combined with the fiber surface through the charge, and the modified aramid fiber has better activity and more binding points, and is helpful to form a denser cross-linking network in the rubber matrix, which can effectively hinder the relative slip in the rubber, thereby enabling better bonding between the rubber and the resin, and improving the overall stability of the system.

[0010] Preferably, the concentration of potassium sulfate in the potassium oleate dispersion is 4-5 g / L.

[0011] By adopting the above technical solution, preferably the concentration of potassium oleate in the potassium oleate dispersion is within the above range, which can further improve the stability of the prepared modified aramid fiber.

[0012] Preferably, the carbon nanotube composite material is prepared by the following method: The modified carbon nanotubes are ultrasonically dispersed in water, and hydrochloric acid is added while stirring to obtain carbon nanotube ammonium salt; montmorillonite is dispersed in water, stirred after heating, carbon nanotube ammonium salt is added, stirring is continued, filtering, washing, and freeze-drying to obtain a carbon nanotube composite material.

[0013] By adopting the above technical scheme, modified carbon nanotubes and montmorillonite are subjected to cation exchange to obtain a self-assembled carbon nanotube composite material with a one-dimensional / two-dimensional structure. The tubular carbon nanotubes help to improve the exfoliation degree of the layered montmorillonite, while the layered montmorillonite can inhibit the agglomeration of the carbon nanotubes, so that the two have a good mutual dispersion effect and can synergistically improve the overall mechanical strength of the system.

[0014] Preferably, the mass ratio of the carbon nanotubes to montmorillonite is 1:(2-2.8).

[0015] By adopting the above technical solution, preferably the mass ratio between carbon nanotubes and montmorillonite is within the above range, which can further improve the comprehensive performance of the prepared carbon nanotube composite material.

[0016] Preferably, the modified carbon nanotubes are prepared by the following method: The method comprises the following steps: mixing ferrous sulfate heptahydrate with water, adding carbon nanotubes, ultrasonicating, adding hydrogen peroxide, stirring and reacting while adding, then filtering under reduced pressure, washing and drying to obtain pretreated carbon nanotubes, mixing anhydrous ethanol with a titanate coupling agent to obtain a titanate coupling agent mixed solution, adding the pretreated carbon nanotubes to the titanate coupling agent mixed solution, heating and stirring to react after ultrasonic oscillation, filtering under reduced pressure, washing and drying to obtain modified carbon nanotubes.

[0017] By adopting the above technical solution, after the surface of the carbon nanotubes is treated with a titanate coupling agent, the grafted organic chain segments reduce the surface energy of the carbon nanotubes, increase the compatibility of the system, and make the dispersion of the carbon nanotubes more uniform. At the same time, the titanate coupling agent also has hydrogen bonds and chemical bonds with the system, which can further improve the overall mechanical properties of the composite material; through the combination of carbon nanotubes and montmorillonite, the overall mechanical properties of the system can be further improved, and the interface adhesion between the aramid fiber and the epoxy resin matrix can be further improved, thereby further improving the bonding performance of the system.

[0018] Preferably, the mass fraction of the titanate coupling agent in the titanate coupling agent mixed solution is 3.5-4.5%.

[0019] By adopting the above technical solution, preferably the mass fraction of the titanate coupling agent in the titanate coupling agent mixed solution is within the above range, which can further improve the stability of the prepared modified carbon nanotubes.

[0020] Preferably, the chopped fiber composite is prepared by the following method: The carbon nanotube composite material is dispersed in anhydrous ethanol, and after ultrasonic treatment, a carbon nanotube composite material dispersion liquid is obtained. The modified aramid fiber is immersed in the carbon nanotube composite material dispersion liquid, and ultrasonic separation is performed. The aramid fiber is taken out and vacuum dried to obtain a chopped fiber composite.

[0021] By adopting the above technical solution, loading the carbon nanotube composite material on the surface of the aramid fiber can effectively improve the interfacial adhesion performance of the composite material, thereby further improving the bonding strength between the core tube materials, thereby improving the overall comprehensive performance of the system.

[0022] Preferably, the concentration of the carbon nanotube composite material in the carbon nanotube composite material dispersion is 9-11 g / L.

[0023] By adopting the above technical solution, preferably the concentration of the carbon nanotube composite material in the carbon nanotube composite material dispersion is within the above range, which can further improve the stability of the prepared chopped fiber composite.

[0024] In the second aspect, the present application provides a safe and environmentally friendly process for processing a rough surface rolled core tube, which adopts the following technical solution: A safe and environmentally friendly process for processing a rough surface rolled core tube, comprising the following steps: After mixing polyvinyl chloride, chloroprene rubber, epoxy resin, chopped fiber composite, dispersant and toughening agent, the mixture is added into a twin-screw extruder for melt blending and granulation, the product is extruded into a mold, impurities on the surface of the core tube are removed, and the core tube with a rough surface is obtained after cutting.

[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. A short-cut fiber composite is added to the system. The short-cut fiber has good mechanical properties. After being combined with the epoxy resin and rubber, the overall mechanical properties of the system can be effectively improved. At the same time, the addition of the short-cut fiber can improve the adhesion between the epoxy resin, thereby further improving the bonding performance between the various components in the system. The modified aramid fiber has the characteristics of high strength, high modulus, high stability and good chemical properties. The carbon nanotube has a high aspect ratio. After the two are compounded, the mechanical strength of the core tube can be further improved. At the same time, the prepared core tube has good green and environmental protection performance; 2. After potassium oleate modifies aramid fiber, it can enhance the compatibility between aramid fiber and rubber matrix, so that the two can be more closely combined. At the same time, it can further improve the mechanical resistance of the composite material. The modified aramid fiber has better activity and more binding points, which helps to form a denser cross-linking network in the rubber matrix, hindering the relative slip of each component in the rubber, thereby improving the overall stability and mechanical properties of the system; 3. After loading the carbon nanotube composite material onto the surface of the aramid fiber, the interfacial bonding performance between the aramid fiber and the epoxy resin and rubber matrix can be further improved, thereby further improving the bonding strength between the core tube materials, thereby improving the overall comprehensive performance of the system. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments: Raw material description: All raw materials in the examples can be obtained from commercial sources; among them, the toughening agent is ethylene-vinyl acetate copolymer (CAS No.: 24937-78-8), and the dispersant is polyvinyl pyrrolidone (CAS No.: 9003-39-8) Example 1 Preparation of modified carbon nanotubes: 100 g of ferrous sulfate heptahydrate was mixed with deionized water. After the ferrous sulfate heptahydrate (CAS No.: 7782-63-0) was dissolved, 10 g of carbon nanotubes was added, and ultrasonic oscillation was performed for 30 min. After ultrasonication, 200 g of hydrogen peroxide was added while magnetic stirring was applied to fully mix the system. The magnetic stirring reaction was maintained for 12 h, and then the filtrate was filtered under reduced pressure and washed with deionized water until the filtrate was neutral. Then, the filtrate was dried in a drying oven at 70° C. for 12 h to obtain the above-treated product. To prepare modified carbon nanotubes, anhydrous ethanol and a titanate coupling agent (CAS No.: 67691-13-8) were mixed to obtain a titanate coupling agent mixed solution with a mass fraction of 3.5%, the pretreated carbon nanotubes prepared above were added to the titanate coupling agent mixed solution, ultrasonically oscillated for 30 minutes, then heated to 70°C, magnetically stirred for reaction for 8 hours, then cooled to 25°C, filtered under reduced pressure, washed with anhydrous ethanol and dried in an oven at 70°C for 12 hours to obtain modified carbon nanotubes.

[0027] Preparation of carbon nanotube composites: 5 g of modified carbon nanotubes were ultrasonically dispersed in 100 g of deionized water, and 10 mL of hydrochloric acid was added while stirring, and the mixture was stirred for 30 min to obtain carbon nanotube ammonium salt. 10 g of montmorillonite was dispersed in 200 mL of deionized water, and the mixture was heated to 80°C and stirred at 300 r / min for 30 min, and carbon nanotube ammonium salt was added, and the temperature was kept stirring for 24 h. After filtering, the mixture was washed with ethanol, and freeze-dried at -20°C for 12 h to obtain a carbon nanotube composite material.

[0028] Preparation of modified aramid fiber: 50 g of aramid fiber was soaked in anhydrous ethanol and ultrasonically treated for 2 hours, filtered with deionized water using a suction filter and washed repeatedly for 5 times, and then dried in a 100°C blast drying oven to obtain the treated aramid fiber; deionized water and potassium oleate (CAS No.: 143-18-0) were mixed, and ultrasonically dispersed at a frequency of 1000 Hz for 20 minutes to obtain a potassium oleate dispersion with a mass concentration of 4 g / L, the treated aramid fiber was added to the potassium oleate dispersion, and modified using a jet low-temperature plasma generator with a frequency of 6 Hz, an air source pressure of 10.29 N, and a treatment time of 10 minutes, and then magnetically stirred at a speed of 60 r / min and a temperature of 80°C for 2 hours, and then the aramid fiber was filtered out, washed and filtered with deionized water, and finally dried in an oven at 80°C to obtain modified aramid fiber.

[0029] Preparation of chopped fiber composites: The carbon nanotube composite material was dispersed in anhydrous ethanol, and after ultrasonic treatment for 45 minutes, a carbon nanotube composite material dispersion with a concentration of 9 g / L was obtained. 40 g of modified aramid fiber was immersed in the carbon nanotube composite material dispersion and ultrasonic dispersion was maintained for 6 minutes. After taking out the aramid fiber, it was vacuum dried at 80°C for 10 hours to obtain a chopped fiber composite.

[0030] Prepare the core tube: 160g of polyvinyl chloride, 40g of chloroprene rubber, 90g of epoxy resin, 30g of chopped fiber composite, 10g of dispersant and 8g of toughening agent were mixed, and added into a twin-screw extruder for melt blending and granulation. The barrel temperature of the extruder was set to 200°C, the head temperature was set to 200°C, the die temperature was set to 190°C, and the speed was set to 40r / min to extrude the product into a mold, remove impurities on the surface of the core tube, and after cutting, a core tube with a rough surface was obtained.

[0031] Example 2 Preparation of modified carbon nanotubes: 100 g of ferrous sulfate heptahydrate was mixed with deionized water. After the ferrous sulfate heptahydrate was dissolved, 10 g of carbon nanotubes was added and ultrasonic oscillation was performed for 30 minutes. After ultrasonication, 200 g of hydrogen peroxide was added while magnetic stirring was performed to fully mix the system. The magnetic stirring reaction was maintained for 12 hours. Then, the system was filtered under reduced pressure and washed with deionized water until the filtrate was neutral. Then, the system was dried in a drying oven at 70°C for 12 hours to obtain pretreated carbon nanotubes. Anhydrous ethanol was mixed with a titanate coupling agent to obtain a titanate coupling agent mixed solution with a mass fraction of 4.5%. The pretreated carbon nanotubes prepared above were added to the titanate coupling agent mixed solution, ultrasonic oscillation was performed for 30 minutes, the temperature was then raised to 70°C, the system was magnetically stirred for reaction for 8 hours, and then the system was cooled to 25°C, filtered under reduced pressure, washed with anhydrous ethanol, and dried in an oven at 70°C for 12 hours to obtain modified carbon nanotubes.

[0032] Preparation of carbon nanotube composites: 3.95 g of modified carbon nanotubes were ultrasonically dispersed in 100 g of deionized water, and 10 mL of hydrochloric acid was added while stirring, and the mixture was stirred for 30 min to obtain carbon nanotube ammonium salt; 11.05 g of montmorillonite was dispersed in 200 mL of deionized water, and the mixture was heated to 80°C and stirred at 300 r / min for 30 min, and carbon nanotube ammonium salt was added, and the temperature was kept stirring for 24 h. After filtering, the mixture was washed with ethanol, and freeze-dried at -20°C for 12 h to obtain a carbon nanotube composite material.

[0033] Preparation of modified aramid fiber: 50 g of aramid fiber was soaked in anhydrous ethanol and ultrasonically treated for 2 hours, filtered with deionized water using a suction filter and washed repeatedly for 5 times, and then dried in a 100°C blast drying oven to obtain the treated aramid fiber; deionized water and potassium oleate were mixed, ultrasonically dispersed at a frequency of 1000 Hz for 20 minutes to obtain a potassium oleate dispersion with a mass concentration of 5 g / L, the treated aramid fiber was added to the potassium oleate dispersion, and modified using a jet low-temperature plasma generator with a frequency of 6 Hz, an air source pressure of 10.29 N, and a treatment time of 10 minutes, followed by magnetic stirring at a speed of 60 r / min and a temperature of 80°C for 2 hours, then the aramid fiber was filtered out, washed and filtered with deionized water, and finally dried in an oven at 80°C to obtain modified aramid fiber.

[0034] Preparation of chopped fiber composites: The carbon nanotube composite material was dispersed in anhydrous ethanol, and after ultrasonic treatment for 45 minutes, a carbon nanotube composite material dispersion with a concentration of 11 g / L was obtained. 40 g of modified aramid fiber was immersed in the carbon nanotube composite material dispersion and ultrasonic dispersion was maintained for 6 minutes. After taking out the aramid fiber, it was vacuum dried at 80°C for 10 hours to obtain a chopped fiber composite.

[0035] Prepare the core tube: 200g of polyvinyl chloride, 60g of chloroprene rubber, 100g of epoxy resin, 40g of chopped fiber composite, 16g of dispersant and 12g of toughening agent were mixed, and added into a twin-screw extruder for melt blending and granulation. The barrel temperature of the extruder was set to 200°C, the head temperature was set to 200°C, the die temperature was set to 190°C, and the rotation speed was set to 40r / min to extrude the product into a mold, remove impurities on the surface of the core tube, and after cutting, a core tube with a rough surface was obtained.

[0036] Example 3 Preparation of modified carbon nanotubes: 100 g of ferrous sulfate heptahydrate was mixed with deionized water. After the ferrous sulfate heptahydrate was dissolved, 10 g of carbon nanotubes was added and ultrasonic oscillation was performed for 30 minutes. After ultrasonication, 200 g of hydrogen peroxide was added while magnetic stirring was performed to fully mix the system. The magnetic stirring reaction was maintained for 12 hours. Then, the system was filtered under reduced pressure and washed with deionized water until the filtrate was neutral. Then, the system was dried in a drying oven at 70° C. for 12 hours to obtain pretreated carbon nanotubes. Anhydrous ethanol was mixed with a titanate coupling agent to obtain a titanate coupling agent mixed solution with a mass fraction of 4%. The pretreated carbon nanotubes prepared above were added to the titanate coupling agent mixed solution, ultrasonic oscillation was performed for 30 minutes, the temperature was then raised to 70° C., the system was magnetically stirred for 8 hours, and then the system was cooled to 25° C., filtered under reduced pressure, washed with anhydrous ethanol, and dried in an oven at 70° C. for 12 hours to obtain modified carbon nanotubes.

[0037] Preparation of carbon nanotube composites: 4.41 g of modified carbon nanotubes were ultrasonically dispersed in 100 g of deionized water, and 10 mL of hydrochloric acid was added while stirring, and the mixture was stirred for 30 min to obtain carbon nanotube ammonium salt; 10.59 g of montmorillonite was dispersed in 200 mL of deionized water, and the mixture was heated to 80°C and stirred at 300 r / min for 30 min, and carbon nanotube ammonium salt was added, and the temperature was kept stirring for 24 h. After filtering, the mixture was washed with ethanol, and freeze-dried at -20°C for 12 h to obtain a carbon nanotube composite material.

[0038] Preparation of modified aramid fiber: 50 g of aramid fiber was soaked in anhydrous ethanol and ultrasonically treated for 2 hours, filtered with deionized water using a suction filter and washed repeatedly for 5 times, and then dried in a 100°C blast drying oven to obtain the treated aramid fiber; deionized water and potassium oleate were mixed, ultrasonically dispersed at a frequency of 1000 Hz for 20 minutes to obtain a potassium oleate dispersion with a mass concentration of 4.5 g / L, the treated aramid fiber was added to the potassium oleate dispersion, and modified using a jet low-temperature plasma generator with a frequency of 6 Hz, an air source pressure of 10.29 N, and a treatment time of 10 minutes, followed by magnetic stirring at a speed of 60 r / min and a temperature of 80°C for 2 hours, then the aramid fiber was filtered out, washed and filtered with deionized water, and finally dried in an oven at 80°C to obtain modified aramid fiber.

[0039] Preparation of chopped fiber composites: The carbon nanotube composite material was dispersed in anhydrous ethanol, and after ultrasonic treatment for 45 minutes, a carbon nanotube composite material dispersion with a concentration of 10 g / L was obtained. 40 g of modified aramid fiber was immersed in the carbon nanotube composite material dispersion and ultrasonic dispersion was maintained for 6 minutes. After taking out the aramid fiber, it was vacuum dried at 80°C for 10 hours to obtain a chopped fiber composite.

[0040] Prepare the core tube: 180g of polyvinyl chloride, 50g of chloroprene rubber, 95g of epoxy resin, 35g of chopped fiber composite, 13g of dispersant and 10g of toughening agent were mixed, and then added into a twin-screw extruder for melt blending and granulation. The barrel temperature of the extruder was set to 200°C, the head temperature was set to 200°C, the die temperature was set to 190°C, and the speed was set to 40r / min to extrude the product into a mold, remove impurities on the surface of the core tube, and after cutting, a core tube with a rough surface was obtained.

[0041] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that when preparing the modified carbon nanotubes, the mass fraction of the titanate coupling agent in the titanate coupling agent mixed solution is 2%.

[0042] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that when preparing the modified carbon nanotubes, the mass fraction of the titanate coupling agent in the titanate coupling agent mixed solution is 6%.

[0043] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that when preparing the carbon nanotube composite material, the amount of modified carbon nanotubes used is 6 g, and the amount of montmorillonite used is 9 g.

[0044] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that when preparing the carbon nanotube composite material, the amount of modified carbon nanotubes used is 3.33 g, and the amount of montmorillonite used is 11.67 g.

[0045] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that when preparing the aramid modified fiber, the mass concentration of potassium oleate in the potassium oleate dispersion is 2 g / L.

[0046] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that when preparing the aramid modified fiber, the mass concentration of potassium oleate in the potassium oleate dispersion is 7 g / L.

[0047] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that when preparing the chopped fiber composite, the concentration of the carbon nanotube composite material in the carbon nanotube composite material dispersion is 6 g / L.

[0048] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that when preparing the chopped fiber composite, the concentration of the carbon nanotube composite material in the carbon nanotube composite material dispersion is 14 g / L.

[0049] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that when preparing the carbon nanotube composite material, the modified carbon nanotubes are replaced with ordinary carbon nanotubes.

[0050] Embodiment 13 Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that when preparing the chopped fiber composite, the carbon nanotube composite material is replaced by montmorillonite.

[0051] Embodiment 14 Example 14 is based on Example 3. The difference between Example 14 and Example 3 is that when preparing the chopped fiber composite, the carbon nanotube composite material is replaced with modified carbon nanotubes.

[0052] Comparative Example 1 Comparative Example 1 is based on Example 3, and in Comparative Example 1, the carbon nanotube composite material is replaced with ordinary carbon nanotubes.

[0053] Comparative Example 2 Comparative Example 2 is based on Example 3, and the aramid fiber is not modified in Comparative Example 2.

[0054] Comparative Example 3 Comparative Example 3 is based on Example 3. In Comparative Example 3, only the modified aramid fiber, the modified carbon nanotube and the montmorillonite are physically mixed to prepare the chopped aramid fiber composite.

[0055] Comparative Example 4 Comparative Example 4 is based on Example 3, and in Comparative Example 4, the chopped fiber composite is replaced with an equal amount of modified aramid fiber.

[0056] Performance testing The following performance tests were performed on the samples of Examples 1-14 and Comparative Examples 1-4: (1) Impact resistance test Based on GB / T 1043.1-2008 as the testing standard, the impact strength performance test was carried out on the samples. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.

[0057] (2) Bending strength test Taking GB / T 9341-2008 as the testing standard, the bending properties of the samples were tested. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.

[0058] Table 1 Performance test results of samples of Examples 1-14 and Comparative Examples 1-4 Data analysis Combined with Table 1, it can be seen that the bending strength of Examples 1-3 is 100Mpa or above, indicating that the core tube prepared in this application has good bending strength, and the impact resistance of Examples 1-3 is 47KJ / m 2 The above indicates that the rolled core tube prepared in the present application has good impact resistance.

[0059] In Examples 4 and 5, when preparing modified carbon nanotubes, the mass fraction of the titanate coupling agent in the carbonate coupling agent mixture is not within the range specified in the present application. When the mass fraction of the titanate coupling agent is too small, it is difficult to further improve the modification effect on the carbon nanotubes, and it is difficult to further improve the mechanical capacity of the carbon nanotubes; when the mass fraction of the titanate coupling agent is too high, the stability of the system will be affected, so the performance of Examples 4 and 5 is reduced.

[0060] When preparing carbon nanotube composite materials in Examples 6 and 7, the mass ratio between the modified carbon nanotubes and montmorillonite is not within the range specified in the present application. When the content of montmorillonite is too much or too little, it is difficult to stably combine with the modified carbon nanotubes in the form of ionic bonds to improve the comprehensive performance of the system. Therefore, the performance of Examples 6 and 7 are both reduced.

[0061] In Examples 8 and 9, when preparing modified aramid fibers, the mass concentration of potassium oleate in the potassium oleate dispersion is not within the range specified in the present application. When the mass concentration of potassium oleate is too low, it is difficult to fully modify the aramid fibers, resulting in a decrease in the interface bonding performance between the aramid fibers and the rubber matrix. At the same time, it is difficult to further improve the compatibility of the aramid fibers, affecting the quality of the product. When the mass concentration of potassium oleate is too high, the stability of the aramid fibers decreases, which also affects the quality of the product. Therefore, the performance of Examples 8 and 9 is reduced.

[0062] In Examples 10 and 11, when preparing the chopped fiber composites, the concentration of the carbon nanotube composite materials in the carbon nanotube dispersion is not within the range specified in the present application. When the content of the carbon nanotube composite material is too small, the content loaded on the aramid fiber decreases, and it is difficult to further improve the viscosity improvement effect of the system; when the concentration of the carbon nanotube composite material is too high, too much carbon nanotube composite material agglomerates, making it difficult to evenly load on the surface of the aramid fiber, affecting the stability of the system. Therefore, the comprehensive performance of Examples 10 and 11 is reduced.

[0063] The dispersion performance of the unmodified carbon nanotubes is reduced, and the compatibility is difficult to improve, so the performance of Example 12 is reduced.

[0064] It is difficult to further synergistically improve the overall mechanical properties of the system only by modifying carbon nanotubes or by combining montmorillonite with modified aramid fibers, so the performance of Examples 13 and 14 are both reduced.

[0065] By only combining ordinary carbon nanotubes with modified aramid, on the one hand, the dispersibility of the unmodified carbon nanotubes decreases, affecting the stability of the system; on the other hand, it is difficult to further improve the interface bonding effect of the aramid fiber, so the performance of Example 1 is reduced.

[0066] The interfacial bonding performance of the untreated aramid fiber is reduced, and it is difficult to stably combine with the rubber matrix, so the performance of Comparative Example 2 is reduced.

[0067] The short-cut aramid fiber composite obtained only by physical mixing is difficult to be further combined by electrostatic force, and the stability of the system is also reduced, so the performance of Comparative Example 3 is reduced.

[0068] The bonding performance of the aramid fiber without the carbon nanotube composite material is reduced, and the compatibility is difficult to be further improved, so the performance of Comparative Example 4 is difficult to be further improved.

[0069] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A safe and environmentally friendly rough surface coiled core tube, characterized by: The composition comprises the following components in parts by weight: 160-200 parts of polyvinyl chloride, 90-100 parts of epoxy resin, 40-60 parts of chloroprene rubber, 30-40 parts of chopped fiber composite, 10-16 parts of dispersant and 8-12 parts of toughening agent; The chopped fiber composite comprises a composite material of modified aramid fiber and carbon nanotube.

2. A safe and environmentally friendly rough surface winding core tube according to claim 1, characterized in that: The chopped fiber composite is prepared by the following method: After mixing water and potassium oleate, a potassium oleate dispersion is obtained, and aramid fiber is added to the potassium oleate dispersion, subjected to plasma modification treatment, and then magnetically stirred. The aramid fiber is then filtered out, washed, and dried to obtain modified aramid fiber.

3. A safe and environmentally friendly rough surface winding core tube according to claim 2, characterized in that: The concentration of potassium sulfate in the potassium oleate dispersion is 4-5 g / L.

4. The safe and environmentally friendly rough surface winding core tube according to claim 1, characterized in that: The carbon nanotube composite material is prepared by the following method: The modified carbon nanotubes are ultrasonically dispersed in water, and hydrochloric acid is added while stirring to obtain carbon nanotube ammonium salt; montmorillonite is dispersed in water, stirred after heating, carbon nanotube ammonium salt is added, stirring is continued, filtering, washing, and freeze-drying to obtain a carbon nanotube composite material.

5. A safe and environmentally friendly rough surface winding core tube according to claim 4, characterized in that: The mass ratio of the carbon nanotubes to the montmorillonite is 1:(2-2.8).

6. The safe and environmentally friendly rough surface winding core tube according to claim 4, characterized in that: The modified carbon nanotubes are prepared by the following method: The method comprises the following steps: mixing ferrous sulfate heptahydrate with water, adding carbon nanotubes, ultrasonicating, adding hydrogen peroxide, stirring and reacting while adding, then filtering under reduced pressure, washing and drying to obtain pretreated carbon nanotubes, mixing anhydrous ethanol with a titanate coupling agent to obtain a titanate coupling agent mixed solution, adding the pretreated carbon nanotubes to the titanate coupling agent mixed solution, heating and stirring to react after ultrasonic oscillation, filtering under reduced pressure, washing and drying to obtain modified carbon nanotubes.

7. A safe and environmentally friendly rough surface winding core tube according to claim 6, characterized in that: The mass fraction of the titanate coupling agent in the titanate coupling agent mixed solution is 3.5-4.5%.

8. The safe and environmentally friendly rough surface winding core tube according to claim 1, characterized in that: The chopped fiber composite is prepared by the following method: The carbon nanotube composite material is dispersed in anhydrous ethanol, and after ultrasonic treatment, a carbon nanotube composite material dispersion liquid is obtained. The modified aramid fiber is immersed in the carbon nanotube composite material dispersion liquid, and ultrasonic separation is performed. The aramid fiber is taken out and vacuum dried to obtain a chopped fiber composite.

9. The safe and environmentally friendly rough surface winding core tube according to claim 8, characterized in that: The concentration of the carbon nanotube composite material in the carbon nanotube composite material dispersion is 9-11 g / L.

10. A processing technology for the safe and environmentally friendly rough surface rolled core tube according to claim 1, characterized in that: The steps include: After mixing polyvinyl chloride, chloroprene rubber, epoxy resin, chopped fiber composite, dispersant and toughening agent, the mixture is added into a twin-screw extruder for melt blending and granulation, the product is extruded into a mold, impurities on the surface of the core tube are removed, and the core tube with a rough surface is obtained after cutting.

Citation Information

Cited By

  • High-strength wear-resistant TPU (thermoplastic polyurethane) sheathed cable and manufacturing process thereof

    CN120784034A